2021
DOI: 10.1029/2021gl092843
|View full text |Cite
|
Sign up to set email alerts
|

A Shorter, Sharper Rainy Season Amplifies California Wildfire Risk

Abstract: California has experienced increasingly severe autumn wildfires over the past several decades, which have exacted a rising human and environmental toll. Recent fire and climate science research has demonstrated a clear link between worsening California wildfires and climate change-mainly though the vegetation-drying effect of rising temperatures and shifting precipitation seasonality. New work by Lukovic et al. 2021 explores observed changes in California's autumn precipitation in greater detail-finding that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 34 publications
0
58
0
4
Order By: Relevance
“…Observations over the past 60 years demonstrate a delayed onset of the rainy season in California (Lukovic et al., 2021). This allows dry conditions to extend into the autumn/winter offshore wind season (Abatzoglou et al., 2021; Swain, 2021), amplifying wildfire risk (Goss et al., 2020). Climate model projections suggest further “sharpening” of the precipitation season (Swain et al., 2018), exacerbating the potential for increased wildfire activity and shortening the timespan between major wildfires and the onset of precipitation.…”
Section: Debris Flow Recurrence Interval As a Pre‐fire Decision Support Toolmentioning
confidence: 99%
“…Observations over the past 60 years demonstrate a delayed onset of the rainy season in California (Lukovic et al., 2021). This allows dry conditions to extend into the autumn/winter offshore wind season (Abatzoglou et al., 2021; Swain, 2021), amplifying wildfire risk (Goss et al., 2020). Climate model projections suggest further “sharpening” of the precipitation season (Swain et al., 2018), exacerbating the potential for increased wildfire activity and shortening the timespan between major wildfires and the onset of precipitation.…”
Section: Debris Flow Recurrence Interval As a Pre‐fire Decision Support Toolmentioning
confidence: 99%
“…Conceptually, the temperature regressor provides a measure of longer term drought stress than the short term monthly timeseries. The precipitation regressor captures the sharpness of precipitation regimes, which has been shown to amplify wildfire risk in California (56). In practice, including these extra regressors improved overall model performance only slightly, but allowed the model to better reproduce both monthly trends, interannual variability, and the observed increase in burn area over the observation period, a large fraction of which has been attributed to climate change (see Figures S7-8).…”
Section: Firementioning
confidence: 99%
“…During the 1970s, 1980s, and 1990s, only 4 large fire cases occurred while there was no large fire case from the 1940s to 1960s. This increasing trend of large wildfire numbers may be associated with longterm fuel conditions, human activity, and climate warming (Goss et al, 2020;Mass and Ovens, 2019;Swain, 2021;Williams et al, 2019). Among these 20 large cases, 7 were caused by lightning, 6 were linked to human related activity, 2 were associated with power lines, 3 were under investigation and 1 was undetermined.…”
Section: Three Large Wildfires In 2018mentioning
confidence: 99%
“…The relationship between long-term increased fires and the warmdry trend is widely mentioned (Goss et al, 2020;Swain, 2021). Williams et al (2019) found that California wildfires experienced a fivefold increase in the annual burned area, mainly due to more than an eightfold increase in summer forest fire extent from 1972 to 2018.…”
Section: Introductionmentioning
confidence: 99%